EFFECT OF TIMING OF ARTIFICIAL INSEMINATION RELATIVE TO SPONTANEOUS ESTRUS ON REPRODUCTIVE PERFORMANCE AND CALF GENDER RATIO IN REPEAT BREEDER HOLSTEIN COWS - T. Bayril; O. Yilmaz; B. Cak (Journal of Animal and Plant Sciences, 2016)
This study was conducted to investigate the effect of the interval between the onset of spontaneous estrus and artificial insemination (AI) on reproductive performance and calf sex ratio in repeat breeder Holstein cows. Two hundred eighty lactating Holstein cows were used in this study. The animals were artificially inseminated at different times (0–6, 7–12, 13–18, or 19–24 h) after the onset of spontaneous estrus. Reproductive performance did not differ between cows inseminated at 0–6 h (n = 70), 7–12 h (n = 70), 13–18 h (n = 70), or 19–24 h (n = 70) after the onset of estrus [pregnancy rate: 0–6 h, 57.1%;7–12 h, 65.7%;13–18 h, 54.3%; and19–24 h, 62.9%; embryonic mortality rate: 0–6 h, 8.5%;7–12 h, 5.7%; 13–18 h, 5.7%; and19–24 h, 7.1%; calving rate: 0–6 h, 48.6%;7–12 h, 60%;13–18 h, 48.6%; and19–24 h, 55.7%; twinning rate: 0–6 h, 2.9%;7–12 h, 0%;13–18 h, 5.7%; and 19–24 h 2.9%; and calf sex ratio (F/M): 0–6 h, 64/36%;7–12 h, 48/52%;13–18 h, 42/58%; and19–24 h, 46/54%; P>0.05]. In general, pregnancy rates of the groups inseminated at different postpartum times differed (P< 0.01) and were higher in the group inseminated at >151 days postpartum. Pregnancy rates were similar in groups inseminated in the second and third parities, but were lower in the group inseminated in the fourth parity. In conclusion, rates of pregnancy, embryonic mortality, calving, and twinning of repeat breeder Holstein cows did not differ between cows subjected to AI at different times after the onset of spontaneous estrus. The timing of AI in repeat breeder cows did not influence the calf sex ratio. Pregnancy rate of repeat breeder cows was influenced by postpartum time and parity number.
Keywords: Repeat Breeder Cow; Calf Gender Ratio; Artificial Insemination Time; Pregnancy Rate